Monetary and Fiscal Policy Strategies for Enhancing Financial Sustainability and Growth in Startups: Insights From Romania’s Ecosystem - Răzvan-George Cotescu; Miruna-Mihaela Vasilca; Edi-CristianDumitra; Cezara-Georgiana Radu (Revista de Studii Financiare, 2025)
Romania’s entrepreneurial ecosystem continues to struggle with significant challenges, including limited access to venture capital, bureaucratic inefficiencies, and fragmented policy execution. Despite the European Union’s support for entrepreneurship, Romania’s startup success rates remain comparatively low. This study investigates the role of fiscal and monetary policies in enhancing financial sustainability and growth in the Romanian startup ecosystem. Using quantitative research methods, such as regression analysis, the research quantifies the impact of key policy interventions, like government funding, tax incentives, and credit access on startup survival and performance. The analysis reveals a robust relationship between policy measures and startup success, with policy impact emerging as the most significant driver. It also highlights the effectiveness of targeted interventions. However, the results showed a certain degree of variability due to regional disparities and limited private-sector participation. These steps aim to bridge financial gaps, reduce inefficiencies, and align Romania’s entrepreneurial ecosystem with best practices seen in EU leaders, such as Germany, France, or Poland. In addition, the study discusses behavioral insights to address cognitive and psychological barriers faced by entrepreneurs and offers a set of possible suggestions for policymakers. Future research should investigate longitudinal and sector-specific effects to further optimize these policies for sustainable startup growth.